1993
DOI: 10.1128/jb.175.21.6810-6821.1993
|View full text |Cite
|
Sign up to set email alerts
|

Separation of outer and cytoplasmic membranes of Fibrobacter succinogenes and membrane and glycogen granule locations of glycanases and cellobiase

Abstract: The outer membrane (OM) of Fibrobacter succinogenes was isolated by a combination of salt, sucrose, and water washes from whole cells grown on either glucose or cellulose. The cytoplasmic membrane (CM) was isolated from OM-depleted cells after disruption with a French press. The OM and membrane vesicles isolated from the extracellular culture fluid of cellulose-grown cells had a higher density, much lower succinate dehydrogenase activity, and sodium dodecyl sulfate-polyacrylamide gel electrophoresis protein pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 59 publications
(22 reference statements)
2
31
1
Order By: Relevance
“…This is in agreement with a previous study that showed major endoglucanase and xylanase activities of strain S85 associated with membrane vesicles in the ECCF of cellulose-grown cultures (16).…”
Section: Discussionsupporting
confidence: 82%
“…This is in agreement with a previous study that showed major endoglucanase and xylanase activities of strain S85 associated with membrane vesicles in the ECCF of cellulose-grown cultures (16).…”
Section: Discussionsupporting
confidence: 82%
“…Since Cel9D cannot hydrolyze cellobiose, it can be presumed that ␤-glucosidases (EC 3.2.1.21) would exert a synergistic effect with Cel9D. Indeed, cellobiase activity has been detected in F. succinogenes (7) and two GH3 ␤-glucosidases were identified in the genome of F. succinogenes (21).…”
Section: Discussionmentioning
confidence: 99%
“…Abbreviations: NS, nonsedimentable extracellular culture fluid; ExOM, extracellular outer membrane; OM, outer membrane; PP, periplasmic fraction. ExOM and PP were prepared as previously described (13). The arrowhead indicates a proteolytic degradation product.…”
Section: Identification Of Cbps In Omsmentioning
confidence: 99%